Using Patient-Generated Health Data From Mobile Technologies for Diabetes Self-Management Support: Provider Perspectives From an Academic Medical Center. (January 2014) - Nundy, Shantanu; Lu, Chen-Yuan E.; Hogan, Patrick; Mishra, Anjuli; Peek, Monica E.
Background: Mobile health and patient-generated health data are promising health IT tools for delivering self-management support in diabetes, but little is known about provider perspectives on how best to integrate these programs into routine care. We explored provider perceptions of a patient-generated health data report from a text-message-based diabetes self-management program. The report was designed to relay clinically relevant data obtained from participants' responses to self-assessment questions delivered over text message. Methods: Likert-type scale response surveys and in-depth interviews were conducted with primary care physicians and endocrinologists who pilot tested the patient-generated health data report in an actual clinical encounter. Interview guides were designed to assess providers' perceptions of the feasibility and utility of patient-generated health data in routine clinical practice. Interviews were audiotaped, transcribed, and analyzed using the constant comparative method. Results: Twelve providers successfully piloted the summary report in clinic. Although only a minority of providers felt the report changed the care they provided (3 of 12 or 25%), most were willing to use the summary report in a future clinical encounter (9 of 12 or 75%). Perceived benefits of patient-generated health data included agenda setting, assessment of self-care, and identification of patient barriers. Major themes discussed included patient selection, reliability of patient-generated health information, and integration into clinical workflow. Conclusion: Providers perceived multiple benefits of patient-generated health data in overcoming common barriers to self-management support in clinical practice and found the summary report feasible and usable in a clinical context.